2017
DOI: 10.1016/j.vacuum.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A study on the thermodynamic changes in the mixture of polypropylene (PP) with varying contents of technological and post-user recyclates for sustainable nanocomposites

Abstract: VK, A study on the thermodynamic changes in the mixture of polypropylene (PP) with varying contents of technological and post-user recyclates for sustainable nanocomposites, Vacuum (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The lower melting peak is attributed to the melting of the high-density polyethylene (PEHD) contamination component, whereas at higher temperature it is assigned to the melting process of the polypropylene (PP) component. Other authors also reported a melting peak around 130 • C when carrying out the thermal analysis by DSC for post-consumer recycled PP, and explained this was due to the HDPE presence in packaging films (extrusion technology) [1,34] or as bottle caps (injection-molded PE-HD) [51]. The degree of crystallinity for polyethylene (PE) was calculated based on the standard melting enthalpy corresponding to 100% crystallization of PE (290 J/g) [11].…”
Section: Dsc Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower melting peak is attributed to the melting of the high-density polyethylene (PEHD) contamination component, whereas at higher temperature it is assigned to the melting process of the polypropylene (PP) component. Other authors also reported a melting peak around 130 • C when carrying out the thermal analysis by DSC for post-consumer recycled PP, and explained this was due to the HDPE presence in packaging films (extrusion technology) [1,34] or as bottle caps (injection-molded PE-HD) [51]. The degree of crystallinity for polyethylene (PE) was calculated based on the standard melting enthalpy corresponding to 100% crystallization of PE (290 J/g) [11].…”
Section: Dsc Measurementmentioning
confidence: 99%
“…Polypropylene (PP) ranks third in the plastic manufacturing field [1], being intensely processed for auto components, fittings, pipes, cables, packaging, electronic items and fibers for concrete reinforcing. Generally, PP shows a low impact, especially at low temperatures, and low strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, highimpact PP (Bahlouli et al 2012;Kozderka et al 2016) can also be recovered with appropriate content ratios. Moreover, there is the possibility of including recycled PP on composites (Izzati Zulkifli et al 2015;Michalska-Pożoga et al 2017) thus improving its life cycle. Despite fillers for the manufacturing of composites, by considering other resins such as PE, Pietrelli et al (2017) also suggest the use of plasticizers to improve mechanical properties of microplastic debris.…”
Section: Implications For the Recovery Of The Marine Plastics Debrismentioning
confidence: 99%
“…Moreover, to the best of our knowledge, there have not been any reports on the improvement of thermal conductivity of polymer-matrix composites (PMCs) reinforced with BN-CFs. Polypropylene (PP) was used as the matrix mainly due to its wide commercial availability and good recyclability [33,34]. In this study, to further contribute to the formation of conductive pathways within the matrix, graphite flakes (GFs) were employed as a cost-effective secondary filler, which can lower the percolation threshold of the fillers due to their two-dimensional geometry.…”
Section: Introductionmentioning
confidence: 99%